Radiographic study of distal radial physeal closure in thoroughbred horses - Vulcano, Luiz Carlos [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Muniz, LMR; Moreira, A. F.; Luna, SPL (Amer Coll Veterinary Radiology, 1997)
Monthly radiography was performed to study distal radial physeal closure in ten male and ten female Throughbred horses. The height, thoracic circumference and metacarpus circumference were also measured, Distal radial physeal closure time was sooner in females than males, and took 701 +/- 37 and 748 +/- 55 days respectively.
Keywords: distal radial epiphyseal closure; radiography; Thoroughbred horse